Structural changes in the agri-food complex: priorities and management mechanisms. (December 2019) - Ermolova, Olga; Yakovenko, Natalia; Kirsanov, Vladimir; Ivanenko, Irina
Abstract: The article is devoted to the analysis of the current state and peculiarities of structural changes in the agri-food complex of Russia. The necessity of modernizing the functional and sectoral structure of the Russian agri-food complex, the transition to an innovative development model in the face of dynamic changes in the external and internal factors of the complex functioning is substantiated. The aim of the study is the theoretical and methodological substantiation of the structural modernization of the agri-food complex of Russia as a priority of its development strategy. The influence of state support and investment on the dynamics of structural indicators of the development of the complex is studied. The necessity of directing the state structural policy in the country's agri-food complex in key areas of the complex development and increasing national competitiveness is proved. Using the input-output method, the effectiveness of state support methods was assessed, which made it possible to evaluate alternative options for the impact of stimulating final demand, volume and structure of state support for industries on GDP growth and individual industries. The tendencies of strengthening the competitive position of Russia in the global agri-food market, especially products of the processing industry, are identified. Promising areas of state regulation are identified, the main of which is the stimulation of the formation of long technological chains of added value based on vertical integration.